Genetic Analyses of the Chimeric CYP11B1 / CYP11B2 Gene in a Korean Family with Glucocorticoid-Remediable Aldosteronism - Lee, Ihn Suk; Kim, Seul Young; Jang, Hye Won; Kim, Min Kyeong; Lee, Ju Hee; Lee, Yun Hyeong; Jo, Young Suk (Journal of Korean medical science, 2010)
Glucocorticoid-remediable aldosteronism (GRA) is an autosomal-dominant inheritable form of hyperaldosteronism with early onset hypertension. GRA is caused by unequal crossing-over of the steroid 11 beta-hydroxylase (CYP11B1) and aldosterone synthase (CYP11B2) genes. As a result of chimeric gene duplication, aldosterone is ectopically synthesized in the adrenal zona fasciculata under the control of adrenocorticotropin. Here, we describe three cases of GRA in a Korean family. The proband-a 21-yr-old female-was incidentally found to have high blood pressure (170/108 mmHg). Her 46-yr-old father had been treated twice for cerebral hemorrhage at the ages of 29 and 39 yr. Her 15-yr-old brother had a 2-yr history of hypertension; however, he was never treated. Their laboratory test results showed normokalemia, hyporeninemia, hyperaldosteronism, and a high plasma aldosterone concentration-to-plasma renin activity ratio. Normal saline loading failed to suppress aldosterone secretion. However, dexamethasone administration effectively suppressed their plasma aldosterone concentrations. Following genetic analyses with PCR and direct sequencing to document the chimeric gene and crossover site, respectively, we identified CYP11B1/CYP11B2 and determined the breakpoint of unequal crossover to be located between intron 2 of CYP11B1 and exon 3 of CYP11B2.